Refletindo sobre a domesticação: afetos e relações de poder entre sujeitos humanos e não humanos no interior da Paraíba. - Nascimento, Joelma Batista do (2016)
Focusing on domesticatory processes, the dissertation seeks to understand how to build modes of relationship and interaction between human and nonhuman animals in rural areas in the interior of Paraíba, Brazil. The research revealed that these relationships and interactions are defined by configurations based on hierarchical principles where the technical and emotional-affective dimensions play a key role. In these configurations individualizing interactions (centered on concrete specimens relations, and not species generic) allow the formation of an evaluative scale regulating the relationship. It favors positions of physical and emotional closeness during handling, as well as distancing strategies (always physical and emotional) for commercialization and slaughter. Thus, affect and use techniques and alienation are not posed as contradictory elements among themselves, but as complementary components.